Nanohardness Measurements of CdSiP2 and ZnGeP2 Chalcopyrite-Type Nonlinear Optical Crystals - Ginka Exner; Aleksandar Grigorov; Elizabeth Ivanova; Peter Schunemann; Vladimir Tassev; Kevin Zawilski; Valentin Petrov (Crystals, 2023)
We study the nanohardness and Young’s modulus of randomly oriented CdSiP2 (CSP) and ZnGeP2 (ZGP) single crystals, grown via the horizontal Bridgman method. CSP and ZGP are the only two pnictide chalcopyrites widely used as nonlinear optical crystals in the mid-IR part of the spectrum. Nanoindentation is employed in the continuous stiffness mode (45 Hz, 2 nm) using a Berkovich tip. Nanohardness values of 9.9 ± 0.2 GPa (Knoop hardness of 905 kg/mm2) for CSP and 11.5 ± 0.1 GPa (993 kg/mm2) for ZGP are derived. For Young’s modulus, we obtain 136 ± 2 GPa (CSP) and 150 ± 2 GPa (ZGP). The trend of increasing hardness with bandgap and melting point of the isostructural CSP and ZGP, as deduced from previous measurements, is not confirmed. The results for ZGP are compared to 2GaP, its binary isoelectronic analog, and the values obtained, 11.0 ± 0.3 GPa for the nanohardness and 154 ± 2 GPa for Young’s modulus, indicate good matching within the accuracy limits.